INFLUENCE OF BLOOD METABOLITES AND METABOLIC HORMONES ON POSTPARTUM OVARIAN ACTIVITY IN COWS - ALl, SARFRAJ; AWASTHl, M K; KHAN, J R; TIWARl, R P; POYAM, M R (The Indian Journal of Animal Reproduction, 2023)
Present investigation was conducted to study the influence of blood metabolites and metabolic hormones on postpartum ovarian cyclic activity in Sahiwal cows. Selected experimental animals (n=18) had normal calving and subsequent normal genital health without apparent history of postpartum metritis and endometritis as assessed by gynaeco-clinical examination. Blood samples were collected from each experimental animal on days 50 and 60 postpartum; and blood glucose and serum concentrations of non-esterified fatty acid (NEFA), insulin, triiodothyronine (T3), thyroxin (T4) and progesterone (P4 ) were determined. Animals were classified as cyclic (P4 > 1 ng/ml) and acyclic (P4 < 1 ng/ml) based on serum progesterone concentration on day 50 and /or day 60 postpartum. An increasing trend of serum progesterone concentration was observed in both cyclic and acyclic animals with increasing postpartum interval though extent of which was greater in cyclic animals. Non-significant differences were observed in blood glucose concentration, serum T3 and T4 concentrations between cyclic and acyclic animals on days 50 and 60 postpartum. Acyclic animals recorded significantly higher (P<0.01) serum NEFA concentration and significantly lower (P <0.05) serum insulin concentration on days 50 and 60 postpartum than in cyclic animals. From the present study it may be concluded that an increased concentration of serum NEFA and a decreased level of serum insulin probably resulted in delay in onset of postpartum ovarian activity in Sahiwal cows.